The sociodemographic spatial structure of Dublin in 1981 - Brady, J.E.; Parker, A.J. (Economic & Social Studies, 1986)
The small area statistics of the 1981 Census of Population are analysed with a view to identifying the spatial patterns associated with the socio-demographic structure of Dublin. Factors identify the Socio-Economic Status structure; the Family Status (on stage in the life cycle) structure; the New Residential Areas (which result from post-1971 planned growth) and the Rented Sector. The factors are described and mapped, indicating the varied spatial structures of these differentiating characteristics of the city. The policy implications of these patterns are discussed. The problems of infrastructural resource allocation are commented upon, particularly in the context of Dublin's highly segmented geography of family status.
Keywords: Demographics - Dublin; Socio-economic structure - Dublin